Intercultural business communication - Gibson, Robert (Oxford University Press, 2002)
This book provides teachers, trainers, and business people with an introduction to the theory and practice of intercultural business communication, and surveys some key cultural dimensions and case studies. The approach is interactive, with exercises to encourage readers to reflect on their own attitudes and experience